Variational Analysis of an Electro-Elasto-Viscoplastic Contact Problem With Friction and Wear - Rimi, Khezzani; Ammar, Tedjani Hadj (Communications in Mathematics and Applications, 2021)
We consider a dynamic contact problem with wear between two elastic-viscoplastic piezoelectric bodies. The contact is frictional and bilateral which results in the wear of contacting surface. The evolution of the wear function is described with Archard's law. We derive variational formulation for the model and prove an existence and uniqueness result of the weak solution. The proof is based on arguments of nonlinear evolution equations with monotone operators, a classical existence and uniqueness result on parabolic inequalities, differential equations and fixed point arguments.
Keywords: Electro-elasto-viscoplastic materials; Internal state variable; Normal compliance; Wear; Evolution equations; Fixed point